Pengembangan Konsep Kompensasi Dosen dengan mekanisme reward/punishment ditopang dengan konsep sustainabilitas keuangan dengan menggunakan Sistem Informasi. (Studi Kasus : Universitas X) - Radiant Victor Imbar (Maranatha University Press, 2019)
The performance of X University in addition to being measured by academic productivity, is also measured by the competence of academic staff. Career development, productivity and performance of X University employees (especially lecturers) is the key to X University development strategies towards 2034. So there is a need to build a fix take home pay compensation concept solution with a more valid concept, more effective as a reward / punishment mechanism, and supported by concepts financial sustainability. In addition, the concept must be implemented to an information system that supports fix take home pay compensation to enter lecturer work plans and provides reports on the results of lecturer achievements each semester.